METHODS OF INCREASING THE ACCURACY OF GEODETIC MEASUREMENTS USING SATELLITE DATA (Web of Technology: Multidimensional Research Journal, 2024)
This study explores methods to enhance the accuracy of geodetic measurements through the integration of satellite data, focusing on GNSS systems, atmospheric error correction models, and machine learning applications. Results demonstrate that multi-constellation GNSS systems (e.g., Galileo, BeiDou) and advanced tropospheric and ionospheric corrections significantly improve horizontal and vertical positioning accuracy. Real-time data augmentation, scalability, and AI-driven error predictions were found to further enhance measurement precision. These findings have broad applications in environmental monitoring, urban planning, and infrastructure development, offering a pathway toward more precise and cost-effective geospatial solutions